The impossibility of perfection Aristotle, feminism, and the complexities of ethics - Slote, Michael A. (New York ; Oxford : Oxford University Press, 2011)
Most people think that the difficulty of balancing career and personal/family relationships is the fault of present-day society or is due to their own inadequacies. Michael Slote argues that the difficulty runs much deeper, that it is due to the essential nature of the divergent goods involved in this kind of choice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aristotle; Perfection; Ethics